La recreación como estrategia activa para mejorar la convivencia escolar (2019)
The main objective of this research was to describe how school coexistence is strengthened through recreation as an active strategy in third grade students of the El Saber Integral Educational Institution. Recreation was used as an activated activation strategy, through enjoyment and recreation, to build spaces for reflection and specific knowledge in which the student develops both cognitive and affective potential and this contributes to the improvement of school life. The work is determined through different recreational activities in which the students made use of different sports and educational materials in order to improve the coexistence of the course, the population is characterized by belonging to a vulnerable neighborhood, since the institution is located located to the south of the municipality of Soledad, through the observation and the application of interviews to the members of the community we managed to realize that the third grade of the present institution had problems of coexistence which affected the academic processes of the students, It shows an improvement within the coexistence relations of the study group, after performing the different recreational activities.